The Influence of Marketing Content and Customer Satisfaction on Brand Image on Instagram My Crepe Social Media - Fitriani Nurbaiska; Buyung Romadhoni; Syarhini Indrayani (Pustaka Digital Indonesia, 2024)
This quantitative study aims to understand the influence of content marketing and customer satisfaction on brand image on My Crepe's Instagram. The sample for this study consists of My Crepe Instagram followers. Quantitative data was obtained through distributed questionnaires related to the problem under study. Data collection was conducted using these questionnaires, which were designed to address the research questions. Both primary and secondary data sources were utilized in this study. Primary data was collected directly from the respondents, while secondary data provided additional context and background information. The research instrument used in this study was a Likert scale method, which allowed for the measurement of respondents' attitudes and opinions on a scale, providing a structured way to capture their perceptions. The research results were analyzed using statistical calculations with the Statistical Package for the Social Sciences (SPSS) version 25. This analysis covered the influence of content marketing and customer satisfaction on My Crepe's Instagram brand image. The findings, discussed in the previous chapters, led to the conclusion that both content marketing and customer satisfaction have a positive and significant impact on the brand image of My Crepe on social media. These findings highlight the importance of strategic content marketing and maintaining high customer satisfaction to enhance brand perception on social media platforms like Instagram. By effectively leveraging these elements, My Crepe can strengthen its brand image, fostering a more robust and engaged follower base. Future research could further explore additional variables or employ different research models to build on these insights and provide a more comprehensive understanding of the factors influencing brand image on social media.